The Differences in The Use of Time Period II between The Dorsal Recumbent Position and The Combination Position in Primigravidian Mothers - Hanifah Hanifah; Wagiyo Wagiyo; Elisa Elisa (Poltekkes Kemenkes Semarang, 2019)
Background: Normal labor is influenced by five factors known as 5P, namely passenge (fetus and placenta), passageway (birth canal), powers (strength of contraction / uterine strength, contraction of the abdominal wall muscles, contraction of the diaphragm, and ligament action) ), psychologic maternal and position maternal. The position of labor is one way that can be done to reduce the risk of prolonged labor or when elongated. The position of labor commonly used is the dorsal recumbent position, but a combination of labor positions can also be performed.Purpose: The aim of this study was to determine the differences in the use of time period II between the dorsal recumbent position and the combination position in primigravidian mothers at Roemani Hospital Muhammadiyah Semarang.Methods: The research method used was Quasy Experiment with the design of the Post Test Only Design Group. The number of samples in this study were 30 respondents who were divided into 2 treatment groups. The sampling technique uses Accidental sampling. Data analysis using Independent t-test.Results: Based on the results of the Independent test the t-test obtained p-value = 0,000 (P 0.05), so that there was a significant difference between the dorsal recumbent position and the combination position of the second stage of labor in primigravidian mothers. The average time period II with the dorsal recumbent position was 24.14 minutes and the average time of the second time with the combination position was 19.71 minutes. The conclusion is that the time period II with the combination position is more effective than dorsal recumbent position.Conclusion: It’s hoped that it can be used as a material consideration to improve the quality of services for midwives or health workers, especially for labor positions so as to shorten the time period II.